2011
DOI: 10.1111/j.1439-0396.2011.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short‐term water restriction in hot season on some blood parameters and immune response to Newcastle disease vaccine of local and commercial layers in the late phase of production

Abstract: Forty-five Hisex commercial layers and forty-five local Saudi breed layers were used to compare and assess the effect of water restriction under hot conditions on blood constituents and immune response to Newcastle disease (ND) vaccine. The trial was divided into three periods: control (7 day), water restriction (14 day) and rehydration (7 day). During water restriction, layers from each breed were divided into three groups that received 0%, 20% and 40% restriction of drinking water relative to the control per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In a study with broilers, creatinine concentrations were shown to decrease after 6 h of water deprivation from approximately 38 to 27 mmol/L, but to rise significantly over the next 42 h period at a linear rate, reaching 65 mmol/L after 48 h of deprivation ( Vanderhasselt et al, 2013 ). In another experiment, laying hens were subjected to various levels of water restriction (0, 20, and 40% restriction) for a 1-wk period ( Alamer and Ahmed, 2012 ). During this time, plasma creatinine concentration was elevated in those experiencing water restriction, suggesting reduced renal functioning ( Alamer and Ahmed, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with broilers, creatinine concentrations were shown to decrease after 6 h of water deprivation from approximately 38 to 27 mmol/L, but to rise significantly over the next 42 h period at a linear rate, reaching 65 mmol/L after 48 h of deprivation ( Vanderhasselt et al, 2013 ). In another experiment, laying hens were subjected to various levels of water restriction (0, 20, and 40% restriction) for a 1-wk period ( Alamer and Ahmed, 2012 ). During this time, plasma creatinine concentration was elevated in those experiencing water restriction, suggesting reduced renal functioning ( Alamer and Ahmed, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another experiment, laying hens were subjected to various levels of water restriction (0, 20, and 40% restriction) for a 1-wk period ( Alamer and Ahmed, 2012 ). During this time, plasma creatinine concentration was elevated in those experiencing water restriction, suggesting reduced renal functioning ( Alamer and Ahmed, 2012 ).…”
Section: Resultsmentioning
confidence: 99%